Innovation of Natural Orchid Cultivation Technology for Tourism Development in Banyunganti Hamlet, Jatimulyo Village, Girimulyo Sub-District, Kulon Progo District, Yogyakarta - Endang Semiarti; Aziz Purwantoro; Ari Indrianto; Aries Bagus Sasongko; Oktaviana Herawati; Asri Fajar Milasari (Universitas Gadjah Mada, 2020)
Orchid is the best tourism icon which focused on nature-based tourism development in Indonesia. Banyunganti Hamlet is one of the tourism villages in Kulon Progo which has a high diversity of orchid species. Regarding this situation, guiding and assistance for villagers which is focused on the introduction of natural orchid species and its character, conventional propagation, and modern propagation by using household-scale tissue culture techniques (sowing seeds and planting) is important to give. The long-term goal for this activity was for empowering women in Dusun Banyunganti in line with the opening of the New Yogyakarta International Airport by the government.